1996
DOI: 10.1002/(sici)1097-0142(19960101)77:1<113::aid-cncr19>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Infiltrating lobular carcinoma of the breast: Clinicopathologic analysis of 975 cases with reference to data on conservative therapy and metastatic patterns

Abstract: Our analysis specifies the clinicopathological features of ILC and confirms that conservation therapy may be an appropriate treatment for this type of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
193
4
22

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(238 citation statements)
references
References 28 publications
19
193
4
22
Order By: Relevance
“…[20][21][22][23] The authors of the original study stressed that this grading system had clinical utility for both invasive lobular carcinoma and special type cancers. This was further validated by the work of Sastre-Garau et al, 24 who showed that histologic grade is as important for prognosis in invasive lobular carcinoma as it is in invasive ductal carcinomas. However, pathologists have been reluctant to utilize it in relation to invasive lobular carcinoma due primarily, it is thought, to the absence of any tubule formation in invasive lobular carcinomas, rendering that dimension of the three-tiered grading system redundant.…”
Section: Discussionmentioning
confidence: 77%
“…[20][21][22][23] The authors of the original study stressed that this grading system had clinical utility for both invasive lobular carcinoma and special type cancers. This was further validated by the work of Sastre-Garau et al, 24 who showed that histologic grade is as important for prognosis in invasive lobular carcinoma as it is in invasive ductal carcinomas. However, pathologists have been reluctant to utilize it in relation to invasive lobular carcinoma due primarily, it is thought, to the absence of any tubule formation in invasive lobular carcinomas, rendering that dimension of the three-tiered grading system redundant.…”
Section: Discussionmentioning
confidence: 77%
“…Although some studies reported limited prognostic value for histological grading of invasive lobular carcinoma, 15 we and others have demonstrated that grading of these tumours, using the Nottingham grading system, is a strong and independent predictor of outcome, which supports the importance of routine assessment of histological grade in invasive lobular carcinoma. [16][17][18][19][20][21] Analysing the three components of grading separately revealed that mitotic count was of more prognostic power than the two other components. 16,21 This raises the question of whether pleomorphic lobular carcinoma as a distinct pathological subtype has any clinical value additional to grading, because conventional grading also includes cellular atypia and mitotic count as components.…”
mentioning
confidence: 99%
“…The tumour characteristics of lobular carcinomas were those already found by Sastre and co-workers and others (SastreGarau et al, 1996;Cristofanilli et al, 2005). Patients diagnosed with lobular invasive carcinomas were significantly older (Sastre-Garau et al, 1996) Because of the frequent use of either exclusive or preoperative radiotherapy, the study of pathological response in our series was not relevant. Bearing in mind the mandatory caution in interpreting clinical response (Bollet et al, 2007), we found that the response to primary chemotherapy was significantly better for ductal invasive carcinomas than for lobular (X50% of clinical response in 60% for ductal vs 47% for lobular; P ¼ 0.04), confirming the notion developed by others that lobular carcinomas responded less than ductal carcinomas to neoadjuvant chemotherapy (Mathieu et al, 2004;Cristofanilli et al, 2005;Tubiana-Hulin et al, 2006;Wenzel et al, 2006;Katz et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…However, data regarding the specific behaviour of invasive lobular carcinomas (ILC), a histological subtype of breast cancers representing 5 -15% of all breast cancer cases, are still scarce in this therapeutic setting. Lobular carcinomas are characterised by a specific morphology with discohesive small cells usually associated with estradiol receptor (ER), progesterone receptor (PR) positivity and with a low proliferation rate (Sastre-Garau et al, 1996). These factors are now well-established predictive markers of poor response to neoadjuvant chemotherapy (Pierga et al, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation